2021
DOI: 10.2147/ijn.s321800
|View full text |Cite
|
Sign up to set email alerts
|

Coating CoCrMo Alloy with Graphene Oxide and ϵ-Poly-L-Lysine Enhances Its Antibacterial and Antibiofilm Properties

Abstract: Introduction:With increases in implant infections, the search for antibacterial and biofilm coatings has become a new interest for orthopaedists and dentists. In recent years, graphene oxide (GO) has been extensively studied for its superior antibacterial properties. However, most of these studies have focused on solutions and there are few antibacterial studies on metal surfaces, especially the surfaces of cobalt-chromium-molybdenum (CoCrMo) alloys. ε-Poly -L-lysine (ε-PLL), as a novel food preservative, has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Although both g-PGA and e-PLL have good biocompatibility, 27,29 their performance in the PP material required further verification, owing to the more stringent safety requirements for tracheal-drug use. We determined the toxicity of the PP material using the live/ dead double staining method after culturing fibroblasts with a PPcontaining medium for 24 h. Fluorescence staining revealed no significant differences in the proportions of dead cells between the PP and control groups (Fig.…”
Section: Biocompatibility Of Pp In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Although both g-PGA and e-PLL have good biocompatibility, 27,29 their performance in the PP material required further verification, owing to the more stringent safety requirements for tracheal-drug use. We determined the toxicity of the PP material using the live/ dead double staining method after culturing fibroblasts with a PPcontaining medium for 24 h. Fluorescence staining revealed no significant differences in the proportions of dead cells between the PP and control groups (Fig.…”
Section: Biocompatibility Of Pp In Vitromentioning
confidence: 99%
“…We have found that epsilon-poly-L-lysine (e-PLL), a natural cationic polypeptide with antibacterial properties, decomposes into lysine in the human body and has high safety levels. [29][30][31] Therefore, we proposed that g-PGA and e-PLL bound by strong ionic bonds can be used to fulfill the wet-adhesion and antibacterial requirements of the airways thus, improving the duration of drug delivery at the site of tracheal epithelial injury and promoting wound repair via slow release of the loaded bioactive drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial alloys can bring durable and stable antibacterial properties ( Ren and Yang, 2017 ). At present, there are many studies on the alloying and antibacterial modification of traditional alloy materials such as stainless steel, Co-Cr alloys, and Ti alloys, and fruitful results have been achieved ( Resnik et al, 2020 ; Guo et al, 2021a ; Wang et al, 2021a ; Lu et al, 2021 ; Watanabe et al, 2021 ). However, these permanently implanted alloys still suffer from unresolved drawbacks, including the risk of poisoning and allergies, stress shielding issues, and secondary surgery for implant removal ( Sumner, 2015 ; Seyhan et al, 2018 ).…”
Section: The Main Pathogens and Prevention Strategies Of Implant-asso...mentioning
confidence: 99%
“…There are numerous studies on traditional alloy materials, including stainless steel, cobalt-chromium (Co-Cr) alloys, and Ti alloys ( Yamanaka et al, 2013 ; Al Jabbari, 2014 ; Li et al, 2014a ; Bekmurzayeva et al, 2018 ; Xue et al, 2020 ). Researchers focused on enhancing the antibacterial effect of these traditional alloys during the early stage and attained fruitful results ( Resnik et al, 2020 ; Guo et al, 2021a ; Wang et al, 2021a ; Lu et al, 2021 ; Watanabe et al, 2021 ). However, as permanent implants, these traditional alloy materials have many problems that need to be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…As a cationic peptide, EPL is capable of binding to negatively charged bacterial cytoplasmic membrane by electrostatic interaction in nature. 44 , 45 The surface modification of EPL enables EPL@PDA NPs to specifically target negatively charged bacteria. Under the irradiation of NIR lasers (808 nm), EPL@PDA NPs can generate local hyperthermia on the surface of MRSA.…”
Section: Introductionmentioning
confidence: 99%